METHODICAL FUNDAMENTALS OF IMPLEMENTATION OF THE CONCEPT "HUMANIZATION OF THE URBAN ENVIRONMENT WITH ARCHITECTURAL-URBAN INFRASTRUCTURE" - Votinov, M.; Smirnova, O.; Chubarova, D. (Municipal economy of cities. Series: «Economy science», 2022)
The article is devoted to the introduction of the concept of "humanization of the urban environment with architectural and urban infrastructure". The scientific article also identifies the features of the formation of architectural and urban infrastructure in the urban environment. The analysis of scientific experience of development of the terminological device in the field of architecture on a question of humanization of the city environment is carried out. Peculiarities of formation of modern urban environment, which includes natural and anthropogenic subsystems, are determined. Regularities of creation of ecopolises as natural and anthropogenic systems are defined. The main problems of the modern urban environment are identified. The main vector of search of new approaches to humanization of architectural and town - planning infrastructure of urban environment is revealed. It is determined that the main direction in improving the living conditions of people and comprehensive improvement of the city environment is primarily environmental. The concept of humanization of the urban environment in the system "work – life – rest – leisure" is developed. The article raises the issue of comfort of people’s lives in the modern urban environment. The main aspects of humanization of the urban environment in the infrastructure of the city in the system of open architectural spaces, human communication with which is carried out through appropriate communication channels (visual, tactile, auditory, olfactory). It is established that such communication channels provide the basic processes of human life in the urban environment. Three groups of tasks of humanization of the modern urban environment are defined, which are solved with the help of color taking into account its psychophysiological, emotional and aesthetic influence and in the system of visual information. It is determined that for a comfortable stay in an urban environment a person needs to satisfy his basic biological (utilitarian), physical-physiological, spiritual-aesthetic, socio-cultural and psychological needs everywhere in all spheres of life.